IMPLICATIONS OF LOYALTY PROGRAMME COMPETITION ON CUSTOMER DECISIONMAKING IN THE BANKING INDUSTRY - Redjeki, Finny; Ayu Amrita, Nyoman Dwika; Faisal, Ijang (KRIEZ ACADEMY : Journal of development and community service, 2024)
Loyalty programs in the banking industry have become an important strategy in maintaining and increasing customer retention, which in turn has a positive impact on bank financial performance. This research examines the effectiveness of loyalty programs in increasing customer retention and their impact on bank financial performance with a focus on the strategies used, factors that influence program success, and their strategic implications. Key strategies analyzed include personalization of incentive offers, use of technology to enhance user experience, and effective communication. Personalization of incentive offers allows banks to tailor loyalty programs according to customer preferences and shopping behavior, increasing their engagement and satisfaction. The use of advanced information technology, such as data analytics and digital platforms, helps banks to optimize user experience, facilitate the redemption of reward points, and provide better customer service. In terms of its impact on bank financial performance, loyalty programs can increase revenue through increasing use of bank products and services, reducing new customer acquisition costs, as well as expanding opportunities for cross-selling and up-selling additional products. Loyal customers tend to have a higher lifetime value and contribute significantly to the bank's net profit margin. Thus, the strategic advice for banks is to continue to innovate in designing and managing their loyalty programs, strengthen compliance with data privacy regulations, and maintain service quality to build customer trust. These steps will help banks not only retain existing customers, but also attract new customers in a competitive market.